Hubungan kontrasepsi suntik dan berat badan dengan tekanan darah pada wanita usia subur - Ramadhini, Natasya; Hidayah, Noor; Sukesih, Sukesih (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Each type of contraception has different benefits and side effects, but hormonal contraceptives containing progesterone, such as injections, generally have side effects in the form of menstrual disorders, weight changes or gain , headaches and increased blood pressure Purpose: To determine the relationship between the use of injectable contraceptives and weight changes with blood pressure in women of childbearing age. Method: This study used an observational analytical design with a retrospective cohort approach and secondary data from medical records. The sample consisted of 80 respondents, comprising 40 users of 1-month contraceptive injections and 40 users of 3-month contraceptive injections. Statistical tests used chi-square. Results: Bivariate analysis showed no statistically significant relationship between injectable contraceptive use and blood pressure, or between weight change and blood pressure (p > 0.05). However, the Relative Risk value indicated that users of 1-month injectable contraceptives had a higher risk of experiencing an increase in blood pressure compared to users of 3-month injectable contraceptives. Conclusion: There was no relationship between injectable contraceptive use and weight change with blood pressure in women of childbearing age at the Batealit Community Health Centre.   Keywords: Blood Pressure; Injectable Contraceptives; Wight.   Pendahuluan: Setiap jenis kontrasepsi memiliki manfaat dan efek samping yang berbeda, namun pada kontresepsi metode hormonal  yang berisi hormon progesteron seperti suntik ini umumnya memiliki efek samping berupa gangguan haid , perubahan atau kenaikan berat badan , sakit kepala dan kenaikan tekanan Tujuan: Untuk mengetahui hubungan penggunaan kontrasepsi suntik dan perubahan berat badan dengan tekanan darah pada wanita usia subur. Metode: Penelitian menggunakan desain analitik observasional dengan pendekatan kohort retroprospektif dan data sekunder dari rekam medis. Sampel berjumlah 80 responden, terdiri dari 40 pengguna kontrasepsi suntik 1 bulan dan 40 pengguna kontrasepsi suntik 3 bulan. Uji statistic menggunakan chi square. Hasil: Hasil analisis bivariat menunjukkan tidak terdapat hubungan yang bermakna secara statistik antara penggunaan kontrasepsi suntik dengan tekanan darah, maupun antara perubahan berat badan dengan tekanan darah (p > 0,05). Meskipun demikian, nilai Relative Risk menunjukkan bahwa pengguna kontrasepsi suntik 1 bulan memiliki risiko lebih tinggi mengalami peningkatan tekanan darah dibandingkan pengguna kontrasepsi suntik 3 bulan. Simpulan: Tidak terdapat hubungan penggunaan kontrasepsi suntik dan perubahan berat badan dengan tekanan darah pada wanita usia subur di Puskesmas Batealit.   Kata Kunci : Berat Badan; Kontrasepsi Suntik; Tekanan Darah.